2013
DOI: 10.1371/journal.pone.0073395
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Psychiatry as a Prospective Career among Medical Students in Their Pre-Clinical Year in China- A Pilot Study

Abstract: ObjectiveTo understand the attitudes among medical students in China toward different medical specialties and to find the factors that influenced their choice of career in psychiatry.MethodsA questionnaire was developed and administered to 287 medical students at the Xiangya Medical College, Central South University in Changsha, China. All the students were asked to rate the importance of five possible factors in choosing a specialty as a vocation: the ability to help patients, interesting and challenging work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The mental health-related stigma could further compound the shortage of mental health resources. Furthermore, in our previous study, less than 2% of medical students chose psychiatry as their first choice of career due to negative attitudes about psychiatry (50). Mental health resources, especially human resources, are inadequate worldwide, particularly in low-income and middle-income countries (51).…”
Section: Discussionmentioning
confidence: 97%
“…The mental health-related stigma could further compound the shortage of mental health resources. Furthermore, in our previous study, less than 2% of medical students chose psychiatry as their first choice of career due to negative attitudes about psychiatry (50). Mental health resources, especially human resources, are inadequate worldwide, particularly in low-income and middle-income countries (51).…”
Section: Discussionmentioning
confidence: 97%
“…Lack of knowledge and lack of clinical experience with patients lead to students’ negative attitudes and stigmatization towards people with mental disorders (Kato, Balhara, Chawla, Tateno, & Kanba, ). Lack of clinical experience in a mental health department would not motivate medical health professionals to specialize in Psychiatry (Wang, Xiang, Hao, & Liu, ). Most of the health professionals’ attitudes are based on their experience (Hugo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two authors reviewed the survey items. Based on a literature review [7,9,13,, they identified 36 student-level factors, including demographic factors, matriculation reasons, and experiential items, that were hypothesized to be associated with the psychiatry career choice (Online Resource 4). Logistic regression analysis was used as the original analysis for variable screening, with the selection of either psychiatry or any other specialty as a career choice as the binary dependent variable.…”
Section: Resultsmentioning
confidence: 99%
“…Based on statistics from the Psychiatry Teaching Steering Committee, the rate of a psychiatry career choice was around 30%. A few studies have evaluated attitudes toward psychiatry and mental illness among Chinese medical students [5][6][7][8][9][10], but studies on psychiatry as a career choice have been scarce. One study showed that approximately 1.6% of fourth-year medical students in Xiangya Medical School chose psychiatry as a career [9].…”
Section: Introductionmentioning
confidence: 99%